2012
DOI: 10.1155/2012/386527
|View full text |Cite
|
Sign up to set email alerts
|

Pleiotropic Protective Effects of Phytochemicals in Alzheimer's Disease

Abstract: Alzheimer's disease (AD) is a severe chronic neurodegenerative disorder of the brain characterised by progressive impairment in memory and cognition. In the past years an intense research has aimed at dissecting the molecular events of AD. However, there is not an exhaustive knowledge about AD pathogenesis and a limited number of therapeutic options are available to treat this neurodegenerative disease. Consequently, considering the heterogeneity of AD, therapeutic agents acting on multiple levels of the patho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
1
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(64 citation statements)
references
References 113 publications
(119 reference statements)
0
62
1
1
Order By: Relevance
“…In contrast to our results, resveratrol is regarded as being a candidate for disease therapies against obesity, diabetes 27) , atherosclerosis 28,29) , Alzheimer's disease 30) and various cancers 31) . Many previous studies have also demonstrated that resveratrol prevents these diseases in animal models, and several clinical studies have been conducted.…”
Section: Resveratrol Failed To Delay the Onset Of Stroke In Shrspcontrasting
confidence: 99%
“…In contrast to our results, resveratrol is regarded as being a candidate for disease therapies against obesity, diabetes 27) , atherosclerosis 28,29) , Alzheimer's disease 30) and various cancers 31) . Many previous studies have also demonstrated that resveratrol prevents these diseases in animal models, and several clinical studies have been conducted.…”
Section: Resveratrol Failed To Delay the Onset Of Stroke In Shrspcontrasting
confidence: 99%
“…Obesity and even pre-diabetes state are well-recognised risk factor for dementia and Alzheimer's disease (Gudala et al 2013;Butterfield et al 2014), and during recent years, suggestions have often made that structurally and functionally diverse secondary plant metabolites are potential therapeutic leads for prevention and cure of diabetes-associated dementia (Davinelli et al 2012;Recio et al 2012;Apetz et al 2014). By far a vast majority of such suggestive reports concentrate on plant polyphenolics with antioxidative properties, and a more recent report concludes that inhibition of acetylcholinesterase could also be involved in memory function improving effects of structurally diverse phytochemicals and plant polyphenolics (Huang et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…It has also be shown that resveratrol inhibits COX1, but does not affect the expression of COX2 (Davinelli et al, 2012). Since nuclear factor-kb (NF-kb) signaling activation also plays an important role in neurodegeneration, a link between Alzheimer's Disease (AD) and the neuroprotective activity of resveratrol is its ability to reduce, in cultured rat astroglioma C6 cells, the expression of genes modulated by NF-kb, such as inducible nitric oxide synthase (iNOS), prostaglandin E2 (PGE2), as well as cathepsin and NO (Kim et al, 2006).…”
Section: Impact Of Resveratrol On Cerebrovascular Diseasesmentioning
confidence: 99%